2016
DOI: 10.1055/s-0041-107985
|View full text |Cite
|
Sign up to set email alerts
|

Optimale Schmerztherapie nach Tonsillektomie: ein ungelöstes Problem

Abstract: Tonsillectomy is one of the most painful surgical procedures. Unfortunately, it is not unusual that the patient hear statement like: "There is no way around" or "You receive already enough pain killers". Asking the anesthetist or the otorhinolaryngologist, one may get to hear: "Pain after tonsillectomy is not a real problem. We have a reliable pain management protocol". In contradiction, many clinical studies are showing that many patients have persistent and even severe pain after tonsillectomy despite postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…A scheduled oral analgesic dosing regimen was also found to be effective to manage pain in children after tonsillectomy. 6 Several studies have been conducted in the past five years to evaluate the potential advantage of local pain control, that is, using local anesthetics and infiltration techniques at the tonsillar fossa to achieve pain relief after tonsillectomy. One study 27 found that postoperative infiltration and packing at the surgical site with bupivacaine significantly reduced the pain associated with tonsillectomy.…”
Section: Analysis Of Postoperative Painmentioning
confidence: 99%
“…A scheduled oral analgesic dosing regimen was also found to be effective to manage pain in children after tonsillectomy. 6 Several studies have been conducted in the past five years to evaluate the potential advantage of local pain control, that is, using local anesthetics and infiltration techniques at the tonsillar fossa to achieve pain relief after tonsillectomy. One study 27 found that postoperative infiltration and packing at the surgical site with bupivacaine significantly reduced the pain associated with tonsillectomy.…”
Section: Analysis Of Postoperative Painmentioning
confidence: 99%
“…Management of pain following tonsil surgery needs to encompass efficacy and safety in the immediate perioperative period and address pain following discharge after surgery with both pharmacological and nonpharmacological interventions. Significant demands are placed on children, caregivers and adult patients, as they are required to make accurate assessments and to administer the correct analgesic dosages [ 1 , 3 , 5 , 16 18 ]. Pain after tonsil surgery is often poorly managed at home, and studies have highlighted problems with inadequate prescription and administration [ 3 , 5 , 16 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant demands are placed on children, caregivers and adult patients, as they are required to make accurate assessments and to administer the correct analgesic dosages [ 1 , 3 , 5 , 16 18 ]. Pain after tonsil surgery is often poorly managed at home, and studies have highlighted problems with inadequate prescription and administration [ 3 , 5 , 16 , 17 , 19 ]. Along with bleeding and dehydration, pain is a common reason for readmission [ 6 , 7 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bei einer prospektiven Kohortenstudie in deutschen Krankenhäusern mit mehr als 50 000 Patienten, bei der Schmerzen am ersten postoperativen Tag von 179 chirurgischen Eingriffen verglichen worden waren, fand sich die TE auf Platz 24 [8]. Schmerztherapie nach TE bleibt weltweit ein relevantes Problem bei Erwachsenen und Kindern [9], [10]: In einer schwedischen Registerstudie mit 18 712 Patienten zeigte sich jüngst, dass 20 % der Kinder nach TE schmerzbedingt außerplanmäßig einen Arzt kontaktierten. Die mittlere Dauer der Analgetikatherapie betrug dabei 7,8 Tage [11].…”
Section: Introductionunclassified